Context-aware design pattern for situated analytics: Blended Model View Controller. (February 2018) - ElSayed, Neven A.M.; Smith, Ross T.; Marriott, Kim; Thomas, Bruce H.
Abstract: This paper presents a context-aware design pattern for situated analytics called Blended Model View Controller. Our approach is an event-driven design, allowing a seamless transition between the physical space and information space during use. The Blended Model View Controller allows common user interface controls to work in tandem with printed information on a physical object by adapting the operation and presentation based on a semantic matrix. Also presented is an authoring tool that has been developed to assign the parameters of the semantic matrix. We demonstrate the use of the design pattern with a set of augmented reality interactions including; pinch zoom, menus, and details-on-demand. We analyse each control to highlight how the physical and virtual information spaces work in tandem to provide a rich interaction environment in augmented reality.